O trabalho do ambiente social no campo da assistência social e os desafios para a afirmação do projeto ético político profissional - Sousa, Izamara Nunes (2019)
This dissertation presents the results of the analysis on the work of the social worker in the field of Social Assistance and the challenges for the affirmation of the Professional Ethical-Political Project. It emphasizes the Social Assistance Policy, an area of greater insertion of the social worker, which, through the implementation of SUAS, enlarges job opportunities for the social worker. It analyzes, in this regard, that despite the expansion of some social facilities such as CRAS and CREAS and, consequently, the insertion of social workers in them, there is a widespread precariousness of the work of the social worker and the conditions in which this work is carried out, which in truths express the dilemmas of a broader social context of dismantling rights historically conquered by the working class. It points out from the field research carried out with the social workers of the CRAS and CREAS of Paço do Lumiar some conclusions, such as: the social worker, as a professional who works with the various expressions of the social issue suffers, therefore, directly or indirectly with the refutations of capital, especially when working with Social Policies, which, especially in the neoliberal program, undergo deep cuts and are shifted from a point of view of the law to a compensatory view. It also points out that despite the progress of the Social Assistance Policy, mainly in legal terms, based on the Federal Constitution, this current situation has assumed a centrality to address the expressions of the social question as a response to social inequality. It also concludes that the Ethical - Political Project of Social Service is fundamental to the profession because it guides professional practice in the perspective of the rights of the working class. However, by having principles that go against the current conjuncture, its effectiveness in the daily professional is a challenge